Unraveling solvent‐dependent hydrogen bonding interaction and excited‐state intramolecular proton transfer behavior for 2‐(benzo[d]thiazol‐2‐yl)‐4‐(9H‐carbazol‐9‐yl)phenol: A theoretical study. Issue 1 (17th December 2022) - Dong, Hao; Jiang, Wenkun; Lv, Gang; Han, Yinghui
Abstract: Organic chemosensors with excited‐state intramolecular proton transfer (ESIPT) behavior have attracted much attention because it has great potential in a wide range of applications. Considering the paramount behavior of excited‐state relaxation, in this work, we mainly focus on deciphering photo‐induced hydrogen bonding effects and ESIPT mechanism for the novel 2‐(benzo[d]thiazol‐2‐yl)‐4‐(9H‐carbazol‐9‐yl)phenol (mCzOH) dye. Considering the effects of different solvents on excited‐state dynamics of mCzOH flurophore, we adopt four solvents with different polarities. Analyses of fundamental structural changes, infrared (IR) vibrational spectra, and core valence partition index between S0 and S1 state, we confirm hydrogen bond OH···N of mCzOH should be enhanced via photoexcitation. Especially, the increase of solvent polarity could promote hydrogen bonding strengthening degree. Intramolecular charge transfer (ICT) resulting from photoexcitation qualitatively facilitates the ESIPT occurrence to a large extent. For further checking and probing into ESIPT mechanism, via constructing potential energy curves (PECs) in four solvents, we clarify the ESIPT behavior for mCzOH. Most worthy of mention is that polar solvent plays critical roles in lowering potential barrier of ESIPT reaction and in facilitating ESIPT process. We not only clarify the detailed excited‐state process, but also present the solvent‐polarity‐dependent ESIPT mechanism for mCzOH fluorophore. Abstract : The S1 ‐state hydrogen bonding strengthening of mCzOH and photo‐induced ICT as well as charge redistribution facilitates the solvent‐polarity‐dependent ESIPT behaviors.